Role of CD4 Counts in HIV Negative Healthy Individuals with Disseminated Infections: A Prospective Study - Tejaswee Banavathu; Subhashree Samantaray; Sewa Ram; Deepak Kumar; Abhishek H. L. Purohit; Satyendra Khichar; Durga S. Meena; Naresh K. Midha; Gopal K. Bohra; Mahendra K. Garg (Preventive Medicine: Research & Reviews, 2025)
Aims: Association of disseminated infections with idiopathic CD4 lymphocytopenia is a lesser-studied entity. Authors aimed to find the occurrence of ICL in immunocompetent patients having disseminated infections. Methods: This prospective study was conducted on HIV-negative patients with age ≥18 years, diagnosed with viral, bacterial, fungal or tubercular disease. CD4 levels were done for all patients at hospitalisation and after 3 months. Results: One hundred and ten HIV-negative patients with an age of 42.7 ± 19.2 years with the diagnosis of sepsis (47.3%), tuberculosis (32.7%), mucormycosis (8.2%), viral (7.3%) and nocardiosis (4.5%) were included. About 38.2% had CD4 counts <300 cells/μl at the time of diagnosis. At the 3rd-month follow-up 11.3% had mortality and 8.5% of patients met ICL criteria. On multivariate logistic regression, higher age (>55 years), CD4 counts <200 cells/μl and high C-reactive protein levels were independent predictors of mortality in these patients. Conclusions: Incorporation of routine CD4 count measurement in patients with disseminated infections can help in predicting ICL and thus preventing complications in such patients.